Haplotype diversity of Nemacheilus pfeifferae on the two sides of the Bukit Barisan Mountain Range, West Sumatra: Haplotype diversity of Nemacheilus pfeifferae - Aidil, Dyta Rabbani; Roesma, Dewi Imelda; Tjong, Djong (Journal of Tropical Life Science, 2025)
Nemacheilus pfeifferae is one of the native species from Sumatra Island. The previous morphological study on Nemacheilus pfeifferae from several locations on the two sides of the Bukit Barisan Mountain Range, West Sumatra, showed a significant differentiation. The Bukit Barisan Mountain Range is considered to contribute to that differentiation. This hypothesis was tested by identifying the haplotype diversity of N. pfeifferae from the two sides of the Bukit Barisan Mountain Range using the cytochrome b gene from mitochondrial DNA. The samples were collected from seven geographical populations consisting of four rivers flowing west and three rivers flowing east of the Bukit Barisan Mountain range. The tissue samples were DNA extracted, DNA amplified, DNA sequenced, and analyzed using molecular software. Overall, the result showed that N. pfeifferae from West Sumatra has a sequence divergence of 0.6%-5.5%. No haplotypes were shared between populations of N. pfeifferae from West Sumatra. N. pfeifferae in West Sumatra has high haplotype diversity and moderate nucleotide diversity. The sequence divergences of N. pfeifferae within the western populations are higher than in the eastern populations. Nemacheilus pfeifferae from the western part of Bukit Barisan has high sequence divergences (2.9%-4.8%) with the eastern part of Bukit Barisan. The phylogenetic tree shows the separation of N. pfeifferae populations on the two sides of the Bukit Barisan Mountain Range. Nemacheilus in Asia forms a polyphyletic group supported by a high bootstrap value. The Bukit Barisan Mountain Range has played a significant role in the presence of genetic variation